The experience of workplace spirituality: do age and educational attainment matter? - Wan Yunan, Wan Rahim; Ahmad, Aminah; Omar, Zoharah (Human Resource Management Academic Research Society, 2017)
We examined the experience of workplace spirituality with respect to its three dimensions namely, meaningful work (sense of purpose in work), sense of community (sense of relationship with others at work), and value allignment (match between employee and organization’s values). We also compare the experience of spirituality among younger and older employees and among those with different levels of educational attainment. Using self-administered survey questionnaires, we collected data from 274 Malaysian public service employees involved in poverty alleviation programs in the rural sector. The experience of workplace spirituality is considerably high for all the three dimensions, especially so for meaningful work. Workplace spirituality did not differ significantly by employee age but differed significantly by employee educational attainment. The experience of workplace spirituality for all the three dimensions were greater among employees with college and university education than their counterparts with high school education. Implications for human resource development and future research are presented.